Evaluation of evoked potentials and lymphocyte subsets as possible markers of multiple sclerosis: one year follow up of 30 patients. Issue 8 (August 1986) - Ghezzi, A; Zaffaroni, M; Caputo, D; Montanini, R; Cazzullo, C L
Abstract : Evoked potentials and T-lymphocyte helper/suppressor ratio (H/S) were evaluated serially together with neurological status in 30 definite multiple sclerosis patients to evaluate their possible role in monitoring disease progression. Evoked potentials in many cases reflected the clinical status of the pathways tested, but some exceptions were observed, probably due to subclinical relapses or physical factors. In some instances the occurrence of subclinical relapses was suggested by increased H/S ratios. Serial H/S values increased in parallel with clinical and subclinical relapses, and seemed to show specific patterns in relation to the type of clinical course (relapsing, stable, chronic progressive). Our results suggest that evoked potentials and H/S ratio serial analysis can contribute to a better assessment of the progress of multiple sclerosis.